Plethon wobec tradycji teologicznej Greków - Kujawa, Anna (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2021)
Byzantine philosopher Georgios Gemistos Pletho (1355–1452) is regarded as the first Philhellene who rejected Christianity and attempted to restore the pogan religion of Hellenic gods. In his last work Books of Laws (Νόμων συγγραφή) he presents his own system of theology based on ancient philosophy and Greek mythology. The aim of the paper is to outline some main features of Plethon’s theology and to show the influence of Greek tradition on it.